1933
DOI: 10.1084/jem.58.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Attempts to Produce Acute Disseminated Encephalomyelitis in Monkeys

Abstract: No evidence was found to support the idea that vaccine virus placed in the cisterna magna is capable of producing an acute disseminated encephalomyelitis with perivascular demyelination either in normal or in partially immune monkeys. A testicular extract (Reynals' factor) did not induce vaccine virus to cause an acute disseminated encephalomyelitis in monkeys. Repeated intramuscular injections of brain extracts and brain emulsions into eight monkeys were followed in two instances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
179
0
12

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 554 publications
(197 citation statements)
references
References 14 publications
4
179
0
12
Order By: Relevance
“…The discovery of EAE in 1933 was marked by its diamond anniversary in 2008 (12,13). Twenty-eight years ago researchers, including one of the senior authors of ref.…”
mentioning
confidence: 99%
“…The discovery of EAE in 1933 was marked by its diamond anniversary in 2008 (12,13). Twenty-eight years ago researchers, including one of the senior authors of ref.…”
mentioning
confidence: 99%
“…The disease exhibits relapsing and remitting symptoms including disturbances in vision, speech, coordination, and cognition as well as weakness, spasticity, and paralysis (1,2). Lymphocytic infiltration in the CNS white matter and immune reactions against myelin Ags indicate an autoimmune etiology for MS (1)(2)(3)(4)(5)(6)(7)(8). Allergic encephalomyelitis was first observed as a side effect of the rabies vaccine prepared from rabbit brains by Pasteur in the 1880s (see Ref.…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…3). Rivers and others showed that the CNS inflammation was caused not by the rabies virus but by immune sensitization to the combination of adjuvant and brain tissue contaminating the vaccine (3,4). Experimental allergic encephalomyelitis (EAE) models in various animal species, typically rodents, were later developed by immunization with myelin proteins in adjuvant or by the adoptive transfer of myelinreactive T cells, causing inflammatory damage to the white matter (1)(2)(3)(4)(5)(6).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
See 1 more Smart Citation
“…These genetic risk factors manifest in autoimmune inflammation, Evidence of the inflammatory nature of MS dates back to 1948, when Elvin Kabat observed that MS patients have abnormally high levels of oligoclonal immunoglobulin in the cerebrospinal fluid (CSF) [4]. Self-antigen directed inflammation is thought to precede development of MS; this relationship has been demonstrated in experimental autoimmune encephalomyelitis (EAE), an animal model of MS [5]. In this animal model, the minimal requirement for inducing CNS inflammation is activation of myelin reactive T cells in the peripheral immune system [6].…”
Section: Introductionmentioning
confidence: 99%